Post-competition blood lactate concentrations in competitive track cyclists. Issue 4 (December 1981) - Burke, E. R.; Fleck, S.; Dickson, T.
Abstract : Blood lactate (BL) concentrations were measured in 19 competitive cyclists after 4 competitive track events (kilometre, individual and team pursuit, and match sprints) during the US National Championships. A total of 34 samples were drawn. Our purpose was to investigate the share of anaerobic metabolism in the various events. The greatest mean BL concentration (16.94 mM/l) was found after the kilometre, with one individual recording a value of 18.22 mM/l. A low correlation coefficient for BL versus total riding time was found in the 6 samples drawn during the kilometre (r=0.51) and the 12 samples drawn during the individual pursuit (r=0.44). BL concentrations in all four events were not significantly different (p<0.05) from each other. High values for BL were found in the match sprints (7 samples, mean 13.65 mM/l) an event lasting approximately 11 seconds. The mean BL in the kilometre (6 samples, 16.94 mM/l), individual pursuit (12 samples, 15.18 mM/l), and team pursuit (5 samples, 12.08 mM/l) compare favourably to the values reported for a variety of exercise modes of similar time, except running. While there is increased muscle mass in running, this fact alone may not explain the lower BL values in cycling. It is suggested that lower BL levels may be attributed to prolonged contraction-relaxation phase during cycling causing decreased blood flow to the leg.